Effects of Crude Palm Oil on the Physico-Chemical Properties of Polyethylene Blown Film - Aung, Min Min (2006)
The influence of small amounts of crude palm oil (CPO) content on the physical and chemical properties of high density polyethylene (HDPE) and linear low-density polyethylene (LLDPE) have been investigated. HDPE and LLDPE containing, 2, 3 and 5% CPO were prepared in a twin-screw extruder. Then, films of 0.2mm thickness were produced by using blown film technique. The melting point of CPO is 35.65°C and melting point of PE is 130-140°C in HDPE and 85-125°C in LLDPE. Thermal observation by Differential Scanning Calorimetry (DSC) is not significant in melting and crystallisation. Similar observation was also presented in storage modulus, tan δ and loss modulus of Dynamic Mechanical Analysis (DMA) results.